The Correlations Between Plasma Fibrinogen With Amyloid-Beta and Tau Levels in Patients With Alzheimer’s Disease - Fan, Dong-Yu; Sun, Hao-Lun; Sun, Pu-Yang; Jian, Jie-Ming; Li, Wei-Wei; Shen, Ying-Ying; Zeng, Fan; Wang, Yan-Jiang; Bu, Xian-Le (Frontiers in Neuroscience, 2021)
Recent studies show that fibrinogen plays a role in the pathogenesis of Alzheimer's disease (AD), which may be crucial to neurovascular damage and cognitive impairment. However, there are few clinical studies on the relationship between fibrinogen and AD. 59 11C-PiB-PET diagnosed AD patients and 76 age- and gender-matched cognitively normal controls were included to analyze the correlation between plasma β-amyloid (Aβ) and tau levels with fibrinogen levels. 35 AD patients and 76 controls with cerebrospinal fluid (CSF) samples were included to further analyze the correlation between CSF Aβ and tau levels with fibrinogen levels. In AD patients, plasma fibrinogen levels were positively correlated with plasma Aβ40 and Aβ42 levels, and negatively correlated with CSF Aβ42 levels. Besides, fibrinogen levels were positively correlated with CSF total tau (t-tau), and phosphorylated tau-181 (p-tau) levels and positively correlated with the indicators of Aβ deposition in the brain, such as t-tau/Aβ42, p-tau/Aβ42 levels. In normal people, fibrinogen levels lack correlation with Aβ and tau levels in plasma and CSF. This study suggests that plasma fibrinogen levels are positively correlated with Aβ levels in the plasma and brain in AD patients. Fibrinogen may be involved in the pathogenesis of AD.